2016
DOI: 10.5334/ijic.2446
|View full text |Cite
|
Sign up to set email alerts
|

Substitution of Hospital Care with Primary Care: Defining the Conditions of Primary Care Plus

Abstract: Objective: To analyse barriers and facilitators in substituting hospital care with primary care to define preconditions for successful implementation.Methods: A descriptive feasibility study was performed to collect information on the feasibility of substituting hospital care with primary care. General practitioners were able to refer patients, about whom they had doubts regarding diagnosis, treatment and/or the need to refer to hospital care, to medical specialists who performed low-complex consultations at g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…The apparent influence of the possibility to request additional diagnostic tests on the referral decision is in accordance with the study by van Hoof et al [28]. In the present study, specialists indicated that they needed diagnostic imaging, such as an X-ray, to diagnose patients.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The apparent influence of the possibility to request additional diagnostic tests on the referral decision is in accordance with the study by van Hoof et al [28]. In the present study, specialists indicated that they needed diagnostic imaging, such as an X-ray, to diagnose patients.…”
Section: Discussionsupporting
confidence: 91%
“…Development of patient profiles for PC+ appears relevant for further optimisation of the program. These profiles can give an indication of patient complaints that are suitable for PC+, which would support GPs in their PC+ referral behavior [28].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rising health care expenditures places the potential for substitution of hospital care towards primary care high on the political agenda. [ 1 ] With the Dutch health care system being one of the most costly in Europe[ 2 ], the ultimate goal for the Dutch health care system to make it more sustainable for the future. [ 3 , 4 ] This may imply substituting tasks to primary care, and preventing unnecessary referrals to secondary care.…”
Section: Introductionmentioning
confidence: 99%